2020
DOI: 10.1096/fj.202000061rr
|View full text |Cite
|
Sign up to set email alerts
|

Influence of FGF23 and Klotho on male reproduction: Systemic vs direct effects

Abstract: Currently, no treatment exists to improve semen quality in most infertile men. Here, we demonstrate systemic and direct effects of Fibroblast growth factor 23 (FGF23) and Klotho, which normally regulate vitamin D and mineral homeostasis, on testicular function. Direct effects are plausible because KLOTHO is expressed in both germ cells and spermatozoa and forms with FGFR1 a specific receptor for the bone‐derived hormone FGF23. Treatment with FGF23 increased testicular weight in wild‐type mice, while mice with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 41 publications
(91 reference statements)
1
20
0
Order By: Relevance
“…The epididymal phenotype of Fgf23 -/- mice does not appear to be mediated via systemic hyperphosphatemia as a high phosphate dietary exposure for weeks did not result in testicular or epididymal microcalcifications or changes in testicular phosphate transporter expression. Instead, we have previously shown that germ cell-specific deletion of Klotho in mice leads to aberrant mineral homeostasis, particularly calcium transport through TRPV5 42 , which may be important as low calcium appears to be protective for inducing microcalcifications in a high phosphate environment. Local testicular mineral levels depend mainly on the presence and activity of specific transporters and sensors of calcium and phosphate in the reproductive organs, rather than on systemic concentrations 43 .…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The epididymal phenotype of Fgf23 -/- mice does not appear to be mediated via systemic hyperphosphatemia as a high phosphate dietary exposure for weeks did not result in testicular or epididymal microcalcifications or changes in testicular phosphate transporter expression. Instead, we have previously shown that germ cell-specific deletion of Klotho in mice leads to aberrant mineral homeostasis, particularly calcium transport through TRPV5 42 , which may be important as low calcium appears to be protective for inducing microcalcifications in a high phosphate environment. Local testicular mineral levels depend mainly on the presence and activity of specific transporters and sensors of calcium and phosphate in the reproductive organs, rather than on systemic concentrations 43 .…”
Section: Discussionmentioning
confidence: 98%
“…Human iFGF23 and total FGF23 (iFGF23 + cFGF23) were measured in duplicates in batched assays using assays from Immutopics (Immutopics, #60-6100, #60-6600) according to the manufacturer’s instructions. The seminal fluid FGF23 measurements in healthy men have been published previously 42 . Total serum calcium and phosphorus levels were determined using Stanbio LiquiColor Kits (Stanbio Laboratory).…”
Section: Methodsmentioning
confidence: 99%
“…Several inbred strains of mice, such as the senescence-accelerated mouse ( 10 , 11 ), and transgenic mice, such as Klotho mice ( 12 , 13 ), have been developed to model accelerated aging in humans. These mice exhibit defects in a wide range of organs (e.g., vessels, lungs, kidney, brain, skin and testes), and thus are poor models to study aging of male germ cells as many interfering systems could be operant.…”
Section: Animal Models For Studying Paternal Agingmentioning
confidence: 99%
“…Genetic defects in klotho have been found to cause vascular calcification, hyperphosphatemia, nephropathy, growth retardation, multi-organ atrophy, and fibrosis ( 8 10 ). Expression of klotho has been detected mainly in the kidney, brain, and pancreas, but also in human germ cells and sperm ( 11 ). The klotho family consists of three members: α-, β-, and γ-klotho ( 12 ).…”
Section: Introductionmentioning
confidence: 99%